Association of waist circumference with outcomes in an acute general surgical unit. Issue 6 (24th April 2017) - Ryan, Thomas; Gosal, Preet; Seal, Alexa; McGirr, Joe; Williams, Nicholas
Abstract : Background: Obesity prevalence is increasing in Australia, particularly in non‐metropolitan areas. The effect of obesity on acute surgical outcomes is not known. We aimed to record waist circumference (WC) (surrogate for obesity) amongst acute surgical unit (ASU) patients in a New South Wales regional hospital, and compare outcome measures (length of stay (LOS), unplanned return to theatre, readmission rates, intensive care unit (ICU) admission and mortality). Methods: Retrospective cohort study of 4 months of consecutive ASU admissions, excluding age <16, pregnancy, out‐of‐area transfer and incomplete data. Patients were classified according to World Health Organization WC definitions as high‐risk or non‐high‐risk (increased‐risk and no‐risk). Results: Of 695 admissions, 512 met the inclusion criteria (47.1% female, average age 52.8 years (SD 22.3)), with 85.1% ( P < 0.001) of females and 69.4% ( P = 0.166) of males having an increased‐ or high‐risk WC. This compares to rates amongst inner regional populations of 71.0% (female) and 66.4% (male). LOS was longer for high‐risk patients (5.0 days versus 3.7 days, P = 0.002). However, the mean age of high‐risk patients was greater (56.6 years versus 46.9 years, P = 0.001) and LOS was longer for those aged ≥60 ( P < 0.001). After controlling for age, high‐risk WC was not associated with any outcome measure, except amongst ICU admissions, where high‐risk patients stayed longer (15.5 days versus 6.8 days, P < 0.001). Conclusion: Increased‐ and high‐risk WC was overrepresented amongst female ASU patients. High‐risk WC was associated with a significantly greater LOS in patients admitted to ICU. High‐risk WC was not associated with other outcomes independent of age. WC is useful for quantifying obesity in the inpatient setting.